Monitoring Volcanic and Tectonic Sandbox Analogue Models Using the Kinect v2 Sensor. Issue 6 (1st June 2022) - Rincón, M.; Márquez, A.; Herrera, R.; Galland, O.; Sánchez‐Oro, J.; Concha, D.; Montemayor, A. S.
Abstract: The measurement of surface deformation in analogue models of volcanic and tectonic processes is an area in continuous development. Properly quantifying topography change in analogue models is key for a useful comparison between experiment results and nature. The aim of this work is to evaluate the capabilities of the simple and cheap Microsoft® Kinect v2 sensor for monitoring analogue models made of granular materials. Microsoft® Kinect v2 is a video‐gaming RedGreenBlue‐Depth device combining an optical camera and an infrared distance measurement sensor. The precision of the device for model topography measurements has been quantified using 64 experiments, with variable granular materials materials and distance to the model. Additionally, we tested the capabilities of averaging several distance images to increase the precision. We have developed a specific software to facilitate the acquisition and processing of the Kinect v2 data in experiment monitoring. Our results show that measurement precision is material dependent: with clear‐colored and fine‐grained materials, a precision ∼1.0 mm for digital elevation models with a 1.6 mm pixel size can be obtained. We show that by averaging ≥5 consecutive images the distance precision can reach values as low as 0.5 mm. To show the Kinect v2 capabilities, we present monitoring results from case study experiments modeling tectonics and volcano deformation. The Kinect v2 achieves lower spatial resolutions and precision than more sophisticated techniques such as photogrammetry. However, Kinect v2 provides a cheap, straightforward and powerful tool for monitoring the topography changes in sandbox analogue models. Key Points: The Kinect v2 sensor provides series of Digital Elevation Models of sandbox models with vertical displacement precisions of 1.0–1.5 mm Free software Kinect Acquisition for Analogue Models (KAM) is a tool for acquiring and averaging the Kinect v2 distance images, improving vertical displacement precision to 0.5 mm Combines Kinect v2 sensor and KAM software provide a cheap, easy and powerful tool for monitoring topography in analogue sandbox models